Photochemical activity of membrane-localised polyketide derived marine natural products. Issue 12 (22nd March 2018) - Powell, Kimberley J.; Richens, Joanna L.; Bramble, Jonathan P.; Han, Li-Chen; Sharma, Pallavi; O'Shea, Paul; Moses, John E.
Abstract: Marine organisms rely upon complex bio-chemical systems to manage photo-induced oxidative damage as part of a sophisticated chemical defense. Using a combination of synthetic chemistry and biophysical techniques, we provide evidence to support the notion that marine derived polyene γ-pyrone metabolites of sacoglossan molluscs become localised at cell membranes where they influence the total absorption of the harmful radiation by the lipid membrane, thereby functioning as sunscreen agents. We also report two new hyperperoxide analogues of the putative polyene biosynthetic precursors that themselves are likely candidate natural products. Graphical abstract: